Imagens ativistas e políticas públicas : uma análise na cidade de Aracaju - Alves, Kênia Dantas (2020)
The emergence of the sustainable development model and its objectives brought a direction to the signatory countries in the process of building public policies aimed at the balance between human beings and nature. In this sense, the presence of public power in conjunction with other social actors, such as non-governmental organizations, is of paramount importance to create policies that suit the needs of people and the environment in which they are inserted.Thus, the activist images understood as a communication tool, when used by environmental NGOs, denounce public problems in order to draw the attention of the public authorities to the implementation of public policies. Among the environmental NGOs in Aracaju mentioned in this research, the Urban Cycle Association presented itself as the only organization that makes use of activist images that denounce problems in the capital's cycle and road systems, and these images are used for the analysis process. Thus, the general objective of this research was to analyze the potential of activist images as subsidies for the development of public policies on urban mobility in Aracaju. The methodology included the image analysis method under three strands: images as a document, narrative and the exercise of seeing. In addition, it used the technique of categorizing images from the captions that subscribe to them. As one of the results, the research showed the inefficiency of the public authorities for the maintenance and expansion of bicycle policies in Aracaju, which impact on the construction of a sustainable city, under the aspect of urban mobility. It is concluded that the activist images, when worked by nongovernmental organizations, are communication tools with great potential to draw the attention of the public power, regarding the transformations of local realities through effective and continuous public policies.